REASONS FOR FAMILY SEPARATION DUE TO GENDER IMBALANCE IN UZBEKISTAN AND MEASURES TO REDUCE DIVORCE - Kayumov Abdulaziz Abduxamidovich (Galaxy International Interdisciplinary Research Journal, 2024)
This article analyzes the socio-legal aspects of the problem of gender equality, which is an integral part of human rights in modern Uzbekistan, as well as issues of gender equality and its impact on the family environment and eliminating gender imbalance. when resolving family disputes.